Combination dabrafenib and trametinib in the management of advanced melanoma with BRAFV600 mutations. (2nd May 2016) - Spain, Lavinia; Julve, Maximilian; Larkin, James
ABSTRACT: Introduction : In the 40–50% of advanced melanoma patients with tumors harboring BRAF V600E and V600 K mutations, BRAF inhibitors such as dabrafenib are a highly effective treatment. However, most patients develop resistance after several months on treatment. The addition of a MEK inhibitor, such as trametinib, to BRAF inhibition mitigates one key pathway of resistance, further increasing response rates and improving survival. Areas covered : This article summarizes the mechanism of action of the combination of dabrafenib and trametinib, its evolution through Phase I, II and III clinical trials and discusses its current use in the management of patients with advanced melanoma. Expert opinion : Combination therapy with dabrafenib and trametinib improves response rate, progression-free survival and overall survival when compared to dabrafenib or vemurafenib alone. The addition of trametinib to dabrafenib changes the adverse event profile, making hyperkeratosis and cutaneous squamous cell carcinomas less common but side effects such as fever and nausea more common. How dabrafenib/trametinib is best sequenced with other effective treatments such as immune checkpoint blockade remains uncertain.